Fetal nuchal edema and developmental anomalies caused by gene mutations in mice - Sugiyama, Akira; Hirashima, Masanori (Frontiers in Cell and Developmental Biology, 2022)
Fetal nuchal edema, a subcutaneous accumulation of extracellular fluid in the fetal neck, is detected as increased nuchal translucency (NT) by ultrasonography in the first trimester of pregnancy. It has been demonstrated that increased NT is associated with chromosomal anomalies and genetic syndromes accompanied with fetal malformations such as defective lymphatic vascular development, cardiac anomalies, anemia, and a wide range of other fetal anomalies. However, in many clinical cases of increased NT, causative genes, pathogenesis and prognosis have not been elucidated in humans. On the other hand, a large number of gene mutations have been reported to induce fetal nuchal edema in mouse models. Here, we review the gene mutants causing fetal nuchal edema with defective lymphatic vascular development, cardiac anomalies, anemia and blood vascular endothelial barrier anomalies in mice. Moreover, we discuss how studies using gene mutant mouse models will be useful in developing diagnostic method and predicting prognosis.